Plasminogen activator inhibitor type 1 regulates microglial motility and phagocytic activity - Jeon, Hyejin (BioMed Central, 2012)
BACKGROUND: Plasminogen activator inhibitor type 1 (PAI-1) is the primary inhibitor of urokinase type plasminogen activators (uPA) and tissue type plasminogen activators (tPA), which mediate fibrinolysis. PAI-1 is also involved in the innate immunity by regulating cell migration and phagocytosis. However, little is known about the role of PAI-1 in the central nervous system. METHODS: In this study, we identified PAI-1 in the culture medium of mouse mixed glial cells by liquid chromatography and tandem mass spectrometry. Secretion of PAI-1 from glial cultures was detected by ELISA and western blotting analysis. Cell migration was evaluated by in vitro scratch-wound healing assay or Boyden chamber assay and an in vivo stab wound injury model. Phagocytic activity was measured by uptake of zymosan particles. RESULTS: The levels of PAI-1 mRNA and protein expression were increased by lipopolysaccharide and interferon-γ stimulation in both microglia and astrocytes. PAI-1 promoted the migration of microglial cells in culture via the low-density lipoprotein receptor-related protein (LRP) 1/Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 axis. PAI-1 also increased microglial migration in vivo when injected into mouse brain. PAI-1-mediated microglial migration was independent of protease inhibition, because an R346A mutant of PAI-1 with impaired PA inhibitory activity also promoted microglial migration. Moreover, PAI-1 was able to modulate microglial phagocytic activity. PAI-1 inhibited microglial engulfment of zymosan particles in a vitronectin- and Toll-like receptor 2/6-dependent manner. CONCLUSION: Our results indicate that glia-derived PAI-1 may regulate microglial migration and phagocytosis in an autocrine or paracrine manner. This may have important implications in the regulation of brain microglial activities in health and disease.